Bioactives From Marine Animals: Potential Benefits for Human Reproductive Health - Hoang, Thanh H.; Liang, Qi; Luo, Xuan; Tang, Youhong; Qin, Jian G.; Zhang, Wei (Frontiers in Marine Science, 2022)
Reproductive and sexual health issues, including infertility and sexual dysfunctions (SD), are common concerns affecting millions of reproductive age worldwide. Scattered literature reports that marine animals such as oysters, sea cucumbers, seahorses and spoon worms have unique bioactive compounds like saponins, steroids, seahorse-derived hydrolysates, polypeptide, oligopeptides and essential trace elements that significantly improve infertility, hormonal imbalance, SD, and impotence. In addition, these compounds have exhibited pharmacological properties against reproductive problems due to diabetes and exposure to electromagnetic fields, cyclophosphamide, or a high exercise load. This review presents the first critical assessment of the advances in understanding and applying bioactives from marine organisms to support human reproductive health. Key knowledge and technical gaps have been identified for future research to improve the lack of in-depth understanding of the mechanism and action of these bioactives in human clinical studies. There is a need to develop simple, selective, low-cost, and scalable processes to isolate and purify individual bioactive compounds for industrial applications. The optimizing culturing and farming conditions for specific bioactive compounds from targeted species are suggested for sustainable production. The review indicates a promising future of extracts and marine-derived bioactives as functional foods in preventing and managing human reproductive health issues, but mechanistic studies and further clinical trials are urgently required to evaluate their efficacy and safety.